IMPLEMENTASI KEBIJAKAN PENGENDALIAN PENYAKIT DEMAM BERDARAH DENGUE DI PUSAT KESEHATAN TALISE KOTA PALU - Massi, Rahmat (Katalogis, 2016)
This study aims to determine the implementation of control policy in reducing dengue fever at   Community Health Centre of Talise in Palu city and identify inhibiting factors. The analysis based on the theory of Edward III  and approached by descriptive qualitative. Seven key informants were determined purposively. Data were collected through observation, interviews and documentation. The study shows that the implementation of the policy to control dengue fever at Community Health Centre of Talise in Palu city has not been effective because of some obstacle factors: the communication aspect, refers to the inconsistency of socialization of dengue  in the community and  inappropriate method; the aspect of resources, namely inadequate allocation of funding, limited infrastructures to control the mosquitoes and the structure of  the bureaucratic, subject to lack of responsibilities of cross-program officers. Whilst disposition factor, which refers to implementers behavior, has been supported the implementation of reducing dengue fever program at Community Health Centre of Talise in Palu city.